2002
DOI: 10.1038/sj.onc.1205970
|View full text |Cite
|
Sign up to set email alerts
|

Muc4/sialomucin complex, the intramembrane ErbB2 ligand, induces specific phosphorylation of ErbB2 and enhances expression of p27kip, but does not activate mitogen-activated kinase or protein kinaseB/Akt pathways

Abstract: Muc4/sialomucin complex (SMC) is a multifunctional glycoprotein complex which can repress apoptosis in transfected tumor cells. Its transmembrane subunit acts as an intramembrane ligand for the receptor tyrosine kinase ErbB2 to induce the phosphorylation of ErbB2 and, by acting synergistically with the ErbB3 ligand neuregulin, can potentiate the phosphorylation of ErbB2 and ErbB3. In the present study we show that Muc4/ SMC alone robustly induces the phosphorylation of ErbB2 to enhance the tyrosine phosphate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(152 citation statements)
references
References 36 publications
7
141
4
Order By: Relevance
“…5, merge). These results confirm our previous studies, which indicate that formation of the Muc4/SMC-ErbB2 complex leads to specific phosphorylation of the ErbB2 (26).…”
Section: Muc4 Translocates Erbb2 To the Apical Surface Where It Is Cosupporting
confidence: 82%
“…5, merge). These results confirm our previous studies, which indicate that formation of the Muc4/SMC-ErbB2 complex leads to specific phosphorylation of the ErbB2 (26).…”
Section: Muc4 Translocates Erbb2 To the Apical Surface Where It Is Cosupporting
confidence: 82%
“…S Inaguma et al kinase signaling pathway (Schroeder et al, 2001;Jepson et al, 2002). However, despite the fact that increased MUC5AC expression correlates with a worse prognosis for patients with lung adenocarcinoma (Yu et al, 1996(Yu et al, , 2005, cholangiocarcinoma (Boonla et al, 2003;Aishima et al, 2006) and PDA (Takikita et al, 2009), a molecular mechanism for MUC5AC in determining the properties of these cancer cells has not been fully elucidated.…”
Section: Gli1-induced Muc5ac Attenuates E-cadherinmentioning
confidence: 99%
“…For instance, the expressions of MUC1, MUC2 and MUC5AC were statistically associated with a shorter survival time for pancreatic cancer patients in the United States (Takikita et al, 2009), suggesting that mucin functions not only to protect the normal epithelial surface from harsh environments but also to regulate cancer cell properties. Indeed, membrane-associated mucins were recently shown to play a crucial role in signal transduction (Schroeder et al, 2001;Jepson et al, 2002;Wen et al, 2003;Hollingsworth and Swanson, 2004;Bafna et al, 2010). However, the role for gel-forming mucins in cancer cells is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, sialo-mucin complex (SMC), a rat homologue of MUC4 has also been shown to play multiple roles in tumour cell biology. SMC/Muc4 acts as a ligand for ErbB2/HER2 inducing its limited phosphorylation (Jepson et al, 2002). The overexpression of SMC results in the suppression of both cell adhesion and immune killing of tumour cells, enhanced tumour growth and potentiation of metastasis (Komatsu et al, 1999(Komatsu et al, , 2000(Komatsu et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%